High School EFL Students’ Attitudes towards Learning English Using Blended Learning during the Pandemic - Febriani, Alfinda; Kuswardani , Rahayu (Al-Lisan: Jurnal Bahasa, 2022)
After the COVID-19 cases were reduced, blended learning was used as a learning method in Indonesia. This study aimed to determine high school EFL students' attitudes about using blended learning to aid them in learning English during the pandemic. This research used a quantitative research design with a survey questionnaire as a data collection method and a Likert scale as the data measurement. The participants were collected by convenience sampling method. They are consisted of 32 senior high school students from SMAN 16 Surabaya, SMAN 20 Surabaya and SMA Muhammadiyah 2 Surabaya. This study used descriptive analysis to analyze the findings. The result showed that high school EFL students in Surabaya presented a neutral attitude toward blended learning. In addition, the students showed the best results for the teacher's learning media and the lowest effects for virtual learning. Based on these findings, high school English teachers should improve their online learning practice since the results showed students’ disinterest in it.